Tinjauan Hukum Ekonomi Syariah Terhadap Praktek Pre Order Album Kpop Pada Akun Instagram “Allaboutmerch.Kpop” - Rossy Akbar Fitriana; Masjupri (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Kpop album pre-order is buying and selling music albums from South Korea by ordering and paying in advance. Instagram account “allaboutmerch.kpop”, an that pre-orders kpop albums, but there are several pre-order albums with incomplete specifications. The purposes of this study are to find out the practice of buying and selling pre-order kpop albums on